Error correction model for analysis of influence of fiscal policy on economic growth in EU - Voda, Alina Daniela; Dobrotă, Gabriela; Dobrotă, Dan; Dumitrașcu, Dănuț Dumitru (Journal of Business Economics and Management, 2022)
Ensuring fiscal sustainability in the Member States of the European Union has become an extremely important goal in the current economic context. The formulation of appropriate policies can lead to fiscal consolidation, and the manifestation of a fiscal shock with direct implications on national budgets and can be mitigated by a rational approach. The aim of this paper is to examine issues related to ensuring fiscal sustainability and to identify the necessary fiscal policy instruments in this regard. Using a data set for EU member states for the period 2000–2019, we researched fiscal policy objectives for economic development and the volume of public and private investment. The error correction model (ECM) was used as a derivative of the autoregressive model with distributed lags (ARDL) to assess the short-term variation of Gross Domestic Product under the influence of seven fiscal indicators. The study highlights the aspects of fiscal policies at EU level as well as the correlation between economic development and the fiscal behaviour of the authorities. We contribute to the existing literature by providing empirical evidence on the existence of a direct relationship between economic growth and the volume of private investment.First published online 01 March 2022